Implementing the principles of project based education in ba-courses - R. . Dreher (Moscow Polytechnic University, 2022)
This report aims to explain why the work with PBL-oriented Learning Arrangements is essential for the education in BA-study-courses and how its extension, PBE (Project-Based-Education), is defined. Using this concept, the report illustrates its typical steps (Lecturer-Education, Curriculum Development and Reflecting PBE-Units). It will show typical methods to implement these steps.